Peran manusia terhadap lingkungan dalam Al-Qur’an dan Bible: Pendekatan intertekstualitas Julia Kristeva - Cahya, Anisa Nilam (Maliki Interdisciplinary Journal, 2024)
This research focused on verses in the Qur'an and Bible that examine the role of humans in the environment. This paper is based on the argument that theological ideas of the world's religions state that God has entrusted humans with the management of their environment. The Qur'an and the Bible describe the same thing by mentioning humans as part of the environment and humans as trust holders in maintaining the environment. However, the main cause of environmental damage is a low awareness of ecological issues. The perversion of awareness toward the environment is crucially a perversion of religious values. As a result, the environment in the Qur'an and the Bible can be understood as the environment and as fellow creations of God, people are the unity of creation. The problems in this study are threefold: (1) how is socialization illustrated? (2) What are all the similarities and differences between the Qur'an and the Bible in representing relationships with the environment? (3) What is the intertextuality analysis relations in the Qur'an and the Bible? This research employed the qualitative method in combined with Julia Kristeva's intertextuality method. This study reveals a connection between the Qur'an and the Bible. The fundamental difference, however, is in how humans work to preserve the environment. This is because the Qur'an specifically links spiritual activities like prayer to environmental repair. There are several transpositions from the Bible text to the Qur'an that include several forms of Julia Kristeva's intertextual principles, namely parallel, modification, and haplology.